Evaluation of Nutrition Knowledge in Female Gaelic Games Players - Michèle Renard; David T. Kelly; Niamh Ní Chéilleachair; Ciarán Ó Catháin (MDPI AG, 2020)
Improvements in nutrition knowledge have been associated with increased carbohydrate consumption and greater adherence to dietary recommendations among female athletes. In order to assess whether nutrition knowledge interventions in female Gaelic games players may be beneficial, it is necessary to first of all investigate current levels of nutrition knowledge in this population. Given that many demographic characteristics have been shown to influence nutrition knowledge, it is also important for these to be investigated. The aims of this study were to evaluate the nutrition knowledge of female Gaelic games players, compare knowledge by players' characteristics and identify players' preferences for information and support. A validated 35-item questionnaire was completed by 328 female Gaelic games players (Age: 23.7 ± 5.0 years). Players' mean nutrition knowledge score was 46.0% ± 11.8% and classified as "poor". Elite players scored greater (+4.5-5.9%, p < 0.05) than subelite players. Players with higher levels of general education, history of formal nutrition education and previous advice from a nutritionist also presented greater nutrition knowledge (+3.7-7.5%, p < 0.05). Future education interventions with female Gaelic games players may lead to beneficial changes in dietary behaviour and would likely benefit from stratifying content based on athletes' demographic characteristics, given the differences observed.